Analisis Kualitas Pelayanan di Perguruan Tinggi Negeri dalam Perspektif Higher Educati0n Performance (HEdPerf) Menggunakan Important Performance Analysis (IPA) - Yuli Purwanto; Wawan Prawono; Ratri Wandha Kirana (Direktorat Riset dan Pengabdian Kepada Masyarakat, 2022)
The purpose of this study was to measure the performance of service qualityby using students' perceptions of service quality performance at theDepartment of Industrial Chemical Engineering, Faculty of VocationalStudies ITS Surabaya Indonesia through the Higher Education Performance(HEdPerf) measurement scale using six structural dimensions consisting ofNon-Academic Aspects, Academic Aspects, Reputation, Access, ProgramIssues, and Understanding. Quantitative descriptive method, questionnairesurvey with Probability Sampling technique, and Proportioned StratifiedRandom Sampling collecti0n technique were used as methods in thisstudy. The results of the analysis using Importance-Performance Analysisshow the similarity of the measurement results between each service itemmeasurement and the measurement of the factor/dimensional structureinstrument. The reputation factor is a top priority for improving servicequality. Academic and Access factors have service quality that must bemaintained. Understanding Program Factors and Problems is the secondpriority for improving service quality. Then non-academic factors indicatethat the quality of service exceeds student expectations.